Microtensile bond strength of a resin cement to glass infiltrated zirconia-reinforced ceramic: The effect of surface conditioning - Amaral, Regina [UNESP]; Özcan, Mutlu; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (Elsevier, 2006)
This study evaluated the effect of three surface conditioning methods on the microtensile bond strength of resin cement to a glass-infiltrated zirconia-reinforced alumina-based core ceramic. Thirty blocks (5×5×4 mm) of In-Ceram Zirconia ceramics (In-Ceram Zirconia-INC-ZR, VITA) were fabricated according to the manufacturer's instructions and duplicated in resin composite. The specimens were polished and assigned to one of the following three treatment conditions (n=10): (1) Airborne particle abrasion with 110 μm Al2O3 particles + silanization, (2) Silica coating with 110 μm SiOx particles (Rocatec Pre and Plus, 3M ESPE) + silanization, (3) Silica coating with 30 μm SiOx particles (CoJet, 3M ESPE) + silanization. The ceramic-composite blocks were cemented with the resin cement (Panavia F) and stored at 37 °C in distilled water for 7 days prior to bond tests. The blocks were cut under coolant water to produce bar specimens with a bonding area of approximately 0.6 mm2. The bond strength tests were performed in a universal testing machine (cross-head speed: 1 mm/min). The mean bond strengths of the specimens of each block were statistically analyzed using ANOVA and Tukey's test (α≤0.05). Silica coating with silanization either using 110 μm SiOx or 30 μm SiOx particles increased the bond strength of the resin cement (24.6±2.7 MPa and 26.7±2.4 MPa, respectively) to the zirconia-based ceramic significantly compared to that of airborne particle abrasion with 110-μm Al2O3 (20.5±3.8 MPa) (ANOVA, P<0.05). Conditioning the INC-ZR ceramic surfaces with silica coating and silanization using either chairside or laboratory devices provided higher bond strengths of the resin cement than with airborne particle abrasion using 110 μm Al2O3. © 2005 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Bond strength; Microtensile test; Silane coupling agent; Silica coating; Surface conditioning methods; Zirconia ceramics; Abrasion; Cements; Cooling water; Distilleries; Glass; Resins; Silanes; Zirconium; Ceramic products; aluminum oxide; glass; In Ceram Zirconia; In-Ceram Zirconia; methacrylic acid derivative; methacryloxypropyltrimethoxysilane; Panavia Fluoro; Panavia-Fluoro; resin; resin cement; Rocatec; silane derivative; silicon dioxide; tooth cement; water; zirconium; zirconium oxide; ceramics; chemistry; comparative study; dental bonding; dental surgery; human; materials testing; surface property; temperature; tensile strength; tooth brushing; tooth prosthesis; Air Abrasion, Dental; Aluminum Oxide; Ceramics; Composite Resins; Dental Bonding; Dental Cements; Dental Polishing; Dental Porcelain; Humans; Materials Testing; Methacrylates; Resin Cements; Silicon Dioxide; Surface Properties; Temperature; Tensile Strength; Water